THE EVOLUTION OF INFORMATION AND COMMUNICATION TECHNOLOGY OF EDUCATION OF STUDENTS AT HIGHER EDUCATIONAL INSTITUTIONS OF UKRAINE IN 90-s XX CENTURY – BEGINNING OF XXI CENTURY - Voronkin, О.С. (Journal of Information Technologies in Education (ITE), 2015)
The article presents results of analysis research of the evolution of information and communication technology of education of students in higher educational institutions of Ukraine with 90-s XX century until today. Based on the analysis of materials of scientific conferences,specialized professional publications in the field of pedagogical sciences and other educational publications, as well as the legal framework, organizational aspects, processes of information and computerization of educational institution historical stages are studied. The evolution of international programs and recommendations on the learning, as well as the national framework of IT specialties are considered. The historical stages are identified and named (1990-e - system support of ICT of education at all levels and the emergence of the first distance learning technologies, 2000-s – development web-based learning technology and others learning technologies). Massive introduction of ICT in the learning process contributed to the emergence of new professions, including training of the teaching staff, support of virtual learning environments,mass realization of concepts of open and lifelong learning as well as the development of international and national standards and recommendations for the teaching of IT-disciplines in the universities